Focus Group Discussion (FGD) “Pencegahan Fatalitas - anisa oktiawati; Ita Nur Itsna; Sri Hidayati (UNIVERSITAS BHAMADA SLAWI, 2020)
The Ministry of Health is promoting community empowerment through the Community Movement (Germas) to care for health, one of which minimizes the death of accident victims, especially on the streets (traffic). Communities that are often exposed to traffic accidents need to gain knowledge and skills in handling emergency cases to minimize the fatality of traffic accident victims before victims get further assistance at the nearest health facility (puskesmas and or hospital). The method of implementation is done by the method of observation, coordination, program socialization, program implementation. From the evaluation results it was found that the success of the target number of FGD participants can be considered very good, given the target number of participants as many as 100 people, while in the implementation of activities that were present as many as 129 people. The ability of participants in mastering the material can be judged quite good (70%), this is because the delivery of material and simulations are short with limited time so that it can cause participants to not understand the material presented by the resource persons. This service program is expected to be sustainable to improve the understanding and skills of citizens from various circles to be able to handle traffic accident victims according to their competence.